2022
DOI: 10.1007/jhep08(2022)164
|View full text |Cite
|
Sign up to set email alerts
|

BPS coherent states and localization

Abstract: We introduce coherent states averaged over a gauge group action to study correlators of half BPS states in $$ \mathcal{N} $$ N = 4 SYM theory. The overlaps of these averaged coherent states are a generating function of correlators and can be written in terms of the Harish-Chandra-Itzykzon-Zuber (HCIZ) integral. We show that this formula immediately leads to a computation of the normalization of two point functions in terms of characters obtained originally in the work of Corl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…Similar integrals have been constructed for the projectors onto representations labelled by a single column or row, with an arbitrary length [53,54]. Another development [55][56][57][58], which is closely related, has shown that many of the results from the combinatorial approach can be reproduced by writing suitable generating functions of coherent states as a matrix integral. In some cases these matrix integrals are related to the well known Harish-Chandra-Itzykson-Zuber integral and can be computed using localization.…”
Section: Jhep01(2023)104mentioning
confidence: 82%
See 1 more Smart Citation
“…Similar integrals have been constructed for the projectors onto representations labelled by a single column or row, with an arbitrary length [53,54]. Another development [55][56][57][58], which is closely related, has shown that many of the results from the combinatorial approach can be reproduced by writing suitable generating functions of coherent states as a matrix integral. In some cases these matrix integrals are related to the well known Harish-Chandra-Itzykson-Zuber integral and can be computed using localization.…”
Section: Jhep01(2023)104mentioning
confidence: 82%
“…Consequently, a promising starting point is an integral representations for the relevant operators. This philosophy was recently employed, in a very similar setting, in [55]. In this article we have obtained these integral representations, for operators dual to a boundstate of two sphere giant gravitons or two AdS giant gravitons.…”
Section: Discussionmentioning
confidence: 92%
“…An insertion of a determinant of this form corresponds to a Giant Graviton brane wrapping a 1-dimensional complex curve, which approaches the boundary of AdS 3 at a point z along the line b = au − m + O(a −1 ), where ad − bc = 1 are the coordinates of SL(2, C). 10 When considering insertions of multiple determinants D(m i ; u i ; z i ) there might be many brane configurations with the same asymptotics controlled by parameters m i , u i , z i .…”
Section: Giant Gravitons and Determinantsmentioning
confidence: 99%
“…A method of computing correlations functions of determinant operators in the large N limit was presented in [43]. Following their prescription 11 (also implemented in [10,22,62]), we fermionize the determinants:…”
Section: Giant Gravitons and Determinantsmentioning
confidence: 99%
See 1 more Smart Citation